Antifungal activity of the essential oils of some medicinal plants against human and plant fungal pathogens - Mafakheri, Hamzeh; Mirghazanfari, Sayid Mahdi (Cellular and Molecular Biology, 2018)
The present study was conducted to assess the antifungal activity of essential oils of medicinal plants Mentha piperita (peppermint), Foeniculum vulgare, Satureja hortensis (Savory), Ferula asafoetida and Cuminum cyminum against Alternaria sp., Bipolaris sorokiniana and Acremonium sclerotigenum. The antifungal activity was evaluated by Broth Microdilution Method. Minimum Inhibitory Concentration (MICs) and Minimum Fungicidal Concentration (MFCs) of the essential oils were compared with Amphotricin B and Captan as standard drug. MIC values for all essential oils were between 1 to 8 mg/mL. MIC value of Fennel essential oil was comparable to MFC value obtained from fungicide Captan. Peppermint essential oil exhibited maximum inhibitory and fungicide activity in concentrations of 2 mg/ml and 4 mg/ml against Alternaria sp. The essential oil was more effective than Fennel against Bipolaris, but MFC values of both essential oils were 4 mg/ml. C. cyminum displayed less susceptibility against all of the fungi. Regarding our finding, peppermint and Fennel oil seem to be a promising solution to control plant diseases.